THE LINGUISTIC ANALYSIS OF TRANSLATING SYNTACTIC UNITS AND WORD COMBINATIONS FROM ENGLISH INTO UZBEK - Shavkieva Maftuna; Daniyorova Yorqinoy (Galaxy International Interdisciplinary Research Journal, 2023)
The article deals with the problem of studying of the main features of the newspaper style, the notion of newspaper headline, translation issues of syntactic rules and structure, syntactic and lexical units and word combinations in newspaper texts. It gives information about the language of mass media, a system of interrelated lexical, syntactic units and grammatical means serving the purpose of informing, instructing and entertaining people.